“I will return/come back to you unrecognized”: The Fate of Poetry of Mother Maria in Post-Soviet Russia and France - Tatiana Viktoroff (Studia Litterarum)
The article examines the history of the reception of mother Maria’s poetry in Soviet and post-Soviet Russia, in France and in Great Britain. It analyses how her image and “hypostasis” became mythologized in Russian and foreign cultures in the context of mother Maria’s personality and her life-creating orientation. The author distinguishes several periods in the perception of mother Maria’s image (1965, 1989, the 2000s), analyzes the most important “portraits” of mother Maria the poet those that influenced generations; traces the changes in researchers’ approaches to the study of her work.